Detailed Natura 2000 and CORINE Biotopes habitat maps of the island of Elba (Tuscan Archipelago, Italy). Issue 3 (26th May 2016) - Viciani, Daniele; Dell'Olmo, Lorella; Ferretti, Giulio; Lazzaro, Lorenzo; Lastrucci, Lorenzo; Foggi, Bruno
Abstract : The island of Elba (Tuscan Archipelago, Italy) Natura 2000 habitat map (1:25, 000) and the CORINE Biotopes habitat map (1:25, 000) were derived from the phytosociological map of Elba integrated with recent studies and field knowledge of the vegetation units. Conventional geographical information system queries were used to manage and select the spatial information. For each map polygon, the following attributes were assigned: (i) habitat typology and (ii) percentage cover of each habitat type. Where multiple habitat types were associated with the same polygon, the percentage cover of each habitat type was estimated. A total of 27 Natura 2000 habitat types and 58 CORINE Biotopes habitat types were identified, these being distributed in single and/or multiple typological units. Distribution and covers of the different habitat types are discussed. The usefulness of this kind of map for monitoring and managing conservation actions is discussed.